2019
DOI: 10.3897/phytokeys.127.36608
|View full text |Cite
|
Sign up to set email alerts
|

Recircumscription of Bredia and resurrection of Tashiroea (Sonerileae, Melastomataceae) with description of a new species T. villosa

Abstract: Bredia (Melastomataceae) is an Asian genus that extends from central and southern mainland China to Taiwan and the Ryukyu islands. Molecular phylogenetic analyses reveal that the type of Bredia is nested in a clade of 20 species, while Tashiroea, a genus previously synonymized in Bredia, falls in another distantly related clade of 10 species. Our morphological survey shows that the two clades can be distinguished by several diagnostic features including leaf indumentum, texture, leaf surface sculpture under SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…A similar pattern has been found to the Melastomateae (Michelangeli et al 2013, Veranso-Libalah et al 2017. Recent phylogenetic studies of the Sonerileae-Dissochaeteae complex have already shown that most genera are not monophyletic and the group needs considerable further study (Zeng et al 2016, Zhou et al 2019a, 2019b.…”
Section: Discussionsupporting
confidence: 73%
“…A similar pattern has been found to the Melastomateae (Michelangeli et al 2013, Veranso-Libalah et al 2017. Recent phylogenetic studies of the Sonerileae-Dissochaeteae complex have already shown that most genera are not monophyletic and the group needs considerable further study (Zeng et al 2016, Zhou et al 2019a, 2019b.…”
Section: Discussionsupporting
confidence: 73%
“…In the recircumscribed Bredia, there are only two species which have axillary inflorescences and flowers with eight isomorphic stamens, i.e. B. plagiopetala and B. gracilis (Zhou et al 2019b). Our new species also shares these two characters, but B. reniformis is easily distinguished from the two previously known species by having glandular-puberulous indumentum on young stem, abaxial surface of young leaf blades and calyx tube (versus puberulous), and flowers with reniform calyx lobes (versus lanceolate, or without prominent lobes) and yellowish (versus purple) anthers with obconical (versus spur-like) dorsal appendages (Chen 1984b, Chen andRenner 2007).…”
Section: Similar Speciesmentioning
confidence: 99%
“…Bredia Blume (Melastomataceae) is an Asian genus distributed from central and southern mainland China to Taiwan and the Ryukyu islands (Chen 1984a, Chen and Renner 2007, Zhou et al 2019b. The generic circumscription of Bredia has long been problematic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and certain species of Phyllagathis Blume in Bredia (Diels 1924(Diels , 1932Merrill and Chun 1940;Li 1944;Chen 1979Chen , 1984Hansen 1992;Chen and Renner 2007). By combining molecular phylogenetic and morphological data, recent studies have provided strong evidence for a new generic limit of Bredia (Zhou et al 2019a(Zhou et al , 2019b(Zhou et al , 2019c. Bredia was redefined as excluding Tashiroea while incorporating seven species previously treated in Phyllagathis (Zhou et al 2019b).…”
Section: Introductionmentioning
confidence: 99%